Iterative learning control for impulsive multi-agent systems with varying trial lengths - Cao, Xiaokai; Fečkan, Michal; Shen, Dong; Wang, JinRong (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, we introduce iterative learning control (ILC) schemes with varying trial lengths (VTL) to control impulsive multi-agent systems (I-MAS). We use domain alignment operator to characterize each tracking error to ensure that the error can completely update the control function during each iteration. Then we analyze the system’s uniform convergence to the target leader. Further, we use two local average operators to optimize the control function such that it can make full use of the iteration error. Finally, numerical examples are provided to verify the theoretical results.